Influence of Carbon Content on Ceramic Injection Molding of Reaction‐Bonded Silicon Carbide. Issue 5 (28th July 2016) - Zhang, Zhao; Zhang, Yujun; Gong, Hongyu; Guo, Xue; Zhang, Yubai; Wang, Xianli; Yu, Jincheng
Abstract : Reaction‐bonded silicon carbide (RBSC) was prepared by ceramic injection molding (CIM) technique with feedstocks containing silicon carbide (SiC), a wax‐based organic system and different amounts of carbon black. As a critical effect of the reaction sintering process, carbon was introduced from the carbon black and the decomposition product of the organic polymers, respectively. This study described the influence of carbon content on the mixing and injection process firstly and then emphasized the debinding process since it played a large role in the process of the pyrolysis of organic. Results indicated that the preferable thermal debinding was performed in N2 and the optimal performance was obtained for RBSC with 7 wt.% of carbon black, with the density of 2.98 g/cm 3, apparent porosity of 0.24%, bending strength of 301.59 MPa and fracture toughness of 4.18 MPa·m 1/2 .